Penerapan Sistem Budidaya Durian Berkelanjutan dan Pengaruhnya terhadap Hasil Produksi (Studi Agro Plalangan) - sanaya, irfan; Akhsana Nadia Arifin; Dian Eni Salamah; Silviyana Asfiyati; Hendra Kusuma; Syarif Mustofa Mashur (SUAN PUBLISHER, 2026)
Durian is a high-value tropical fruit with increasing market demand, yet productivity in smallholder farms often remains suboptimal due to conventional cultivation practices. This study analyzes the implementation of a sustainable durian cultivation system at Agro Plalangan, Semarang, and its impact on plant productivity, soil fertility, and ecosystem resilience. Using a qualitative descriptive approach with a case study method, data were collected through participant observation, in-depth interviews with eight purposively selected informants, and documentation. The findings reveal that the applied cultivation practices emphasize resource efficiency and sustainability principles through balanced use of organic and inorganic fertilizers, drip irrigation, and eco-friendly pest and weed management without synthetic chemicals. The avoidance of chemical fruit stimulants helps maintain plant physiological health and extend productive lifespan. A gradual three-year transition from conventional to organic farming successfully improved soil structure and enhanced plant resistance to extreme weather variations. Moreover, the adoption of multiple durian varieties such as Musang King, Montong, Malika, and Bawor strengthened genetic diversity and supported germplasm conservation. This study concludes that sustainable durian cultivation effectively balances ecological, economic, and social dimensions, providing a replicable model for environmentally friendly durian farming in Indonesia while contributing to long-term agricultural sustainability and food security